Airflow Obstruction in Young Adults in Canada - Manal Al-Hazmi; Kate Wooldrage; Nicholas R Anthonisen; Margaret R Becklake; Dennis Bowie; Moira Chan-Yeung; Helen Dimich-Ward; Pierre Ernst; Jure Manfreda; Malcolm R Sears; Hans C Siersted; Lamont Sweet; et al. (Canadian Respiratory Journal)
OBJECTIVE: Airflow obstruction is relatively uncommon in young adults, and may indicate potential for the development of progressive disease. The objective of the present study was to enumerate and characterize airflow obstruction in a random sample of Canadians aged 20 to 44 years.